(untitled) (Research, Society and Development, 2020)
This study aimed to identify the weaknesses and potentialities about the teaching career in higher education in the perception of nursing students. It was a qualitative, exploratory-descriptive research, carried out in a federal public university in the extreme south of the country. The data collection was carried out in July 2017 with 27 participants, through semi-structured interview with open and closed questions. . The data were analyzed through textual discursive analysis, with two categories emerging: Weaknesses and Potentialities about the teaching career from the perspective of nursing students. It was possible to observe that the weaknesses identified are found in teacher training and that the potential identified by academics should be increasingly encouraged.